2017
DOI: 10.1111/jfb.13358
|View full text |Cite
|
Sign up to set email alerts
|

The effects of environmental salinity on the growth and physiology of totoaba Totoaba macdonaldi and shortfin corvina Cynoscion parvipinnis

Abstract: Totoaba Totoaba macdonaldi and shortfin corvina Cynoscion parvipinnis, were acclimated and reared together at salinities of 0, 2, 5, 10, 20 and 35 for 56 days. Initial overall mean ± s.d. body masses of 67·6 ± 7·1 g T. macdonaldi and 37·3 ± 3·1 g C. parvipinnis increased to final overall masses of 217·4 ± 30·3 and 96·5 ± 16·5 g, respectively, at the end of the study. Totoaba macdonaldi was not able to tolerate salinities of 0 and 2 and C. parvipinnis of 0. In contrast, both species had 100% survival at salinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 72 publications
3
2
0
Order By: Relevance
“…The first notable aspect of the current study is that the survival rate of meagre was significantly affected by the rearing salinity with the lowest value at 8‰. This result concurs with the findings (González‐Félix, Perez‐Velazquez, & Cañedo‐Orihuela, ) for other euryhaline species ( Totoaba macdonaldi and Cynoscion parvipinnis ) reared under different salinity levels (from 2‰ to 35‰). The recorded lower survival rate was at salinities below iso‐osmotic levels (12.3‰ and 13.4‰ respectively) whereas T. macdonaldi struggled to survive at 5‰, but 100% mortality was observed at 2‰.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The first notable aspect of the current study is that the survival rate of meagre was significantly affected by the rearing salinity with the lowest value at 8‰. This result concurs with the findings (González‐Félix, Perez‐Velazquez, & Cañedo‐Orihuela, ) for other euryhaline species ( Totoaba macdonaldi and Cynoscion parvipinnis ) reared under different salinity levels (from 2‰ to 35‰). The recorded lower survival rate was at salinities below iso‐osmotic levels (12.3‰ and 13.4‰ respectively) whereas T. macdonaldi struggled to survive at 5‰, but 100% mortality was observed at 2‰.…”
Section: Discussionsupporting
confidence: 92%
“…The current results agree with the findings of Castillo‐Vargasmachuca et al () for spotted rose snapper, Lutjanus guttatus . However, crude protein and fat content did not seem to be sensitive indicators of osmotic stress for other marine species, such as C. parvipinnis and T. macdonaldi (González‐Félix et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the hypertonic environment, fish in isotonic environments could store more energy to use for growth, and Qiang et al (8) have found that 8 ‰ salinity near the isotonic state of GIFT. Similarly, our results parallel those reported by Likongwe et al (39) and González-Félix et al (40) , in which the highest growth rate of fish was observed at salinities close to the isosmotic point compared with freshwater and seawater, which might also be the explanation why GIFT juveniles have higher growth performance under 8 ‰ salinity.…”
Section: Discussionsupporting
confidence: 92%
“…The HSI (1.2-1.6%), GSI (0.08-0.53%) and VSI (7.3-9.5%) reported in this study are comparable to values reported in the literature for these and other sciaenids; for C. parvipinnis, HSI and VSI values ranging from 0.9-2.6% and from 3.7-5.9%, respectively [35], and HSI values ranging from 2.2-2.9% for C. othonopterus [27] have been reported. For other sciaenids like Totoaba macdonaldi, also endemic to the Gulf of California, HSI values ranging from 1.6-2.2% and VSI of 3.6-4.5% [35] have been reported, as well as HSI ranging from 1.33-1.96% for Sciaenops ocellatus [36]. Although comparable, differences between the observed and reported values may be explained by the size differences, since the values reported in the previous studies corresponded mostly to juvenile fish.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, this section was exclusively used to estimate the optimum temperature and pH for enzymatic activity [34]. The analyses were also run in triplicate samples, and each triplicate sample and its blank were run in duplicates, adjusting the incubation temperature to 20,25,30,35,40,45,50,55,60,65,70,75,80,85 and 90°C, whereas the pH was evaluated substituting the buffer in the substrate solution according to the pH evaluated; a 100 mM citrate-NaOH buffer was used for pH 6.0, a 100 mM Tris-HCl buffer for pH 7.0 to 9.0 and a 100 mM glycine-NaOH buffer for pH 10. The temperature for incubation was also adjusted to 65°C for C. parvipinnis and C. xanthulus and to 60°C for C. othonopterus because, at these values, trypsin activity was observed to be optimal in the previous test.…”
Section: Trypsinmentioning
confidence: 99%